Modelo de negocio: galpón con condiciones ambientales autonomamente controladas e integración de Internet de las cosas (IoT) para el monitoreo remoto en plataforma web (2022)
The use of traditional methods for monitoring and control of heating, ventilation, lighting, relative humidity and ammonia concentration in the spaces dedicated to the rearing and raising of broilers, are some of the major limitations for the execution of the activities related to poultry farming in various regions, negatively affecting the economic development of small poultry farmers in the country. Currently the systems for the control and monitoring in the execution of the activities of rearing and raising of broilers are implemented in sheds with high density of birds and considerably large areas, in addition to equipment and adaptations that are expensive for their implementation. This project aims to design a business model based on the Design Thinking methodology that includes the construction of a prototype of a shed at 1:10 scale in meters, with controlled environmental conditions and the possibility of remote monitoring of environmental conditions, that allow the future optimal development of poultry activities, also incorporating technologies based on the Internet of Things (IoT).